Say it out loud : a novel - Schumacher, Ashley (Del Ray, an imprint of Random House, 2025)
"Juniper Green doesn't believe in magic anymore. Not since her mom died, her dreams of a publishing career fizzled, and her podcast--the one bright spot in her life--was stolen out from under her. Now, at thirty-two, she's living in her dad's spare room and wondering if life peaked when she was a teenager with a stack of vampire books and an unhealthy obsession with enigmatic immortals. Then comes the email: an invitation to audition for the lead role in the audio drama adaptation of The Meadow, the wildly popular vampire romance series that defined her teenage years. It's a dream opportunity--until she learns her co-star is James Neely, the brooding, talented actor who played Romeo to her Juliet in a one-night-only college show before breaking her heart and disappearing from the stage and her life . . . right along with the magic. To save the project (and her career), Juniper and James must revive their onstage chemistry, playing The Meadow's star-crossed lovers for the microphones and social media alike. But as the lines between performance and reality blur, Juniper is left wondering: Can you rewrite the ending of a story you thought was over? Because love, like magic, is a fragile thing to lose .. . and to find again"--